Cell-Free Cryopreserved Biological Agents for Cardiac Protection in Autoimmune Myocarditis: A Morphofunctional Animal Model Study - Hladkykh, Fedir V; Liadova, Tetiana I; Komorovsky, Roman R (Scripta Medica, 2025)
Background/Aim: Autoimmune myocarditis (AIM) is a condition characterised by inflammation of the heart muscle, which can lead to heart failure. The development of effective treatments is crucial for improving cardiac function and recovery. Cell-free cryopreserved biological agents (CF-CBAs), including cell-free placenta extract (CEP), cell-free spleen extract (CES) and mesenchymal stem cell-conditioned medium (CM-MSC), have shown promise in preclinical models for their potential to improve heart function in autoimmune myocarditis. This study aimed to evaluate the efficacy of CEP, CES and CM-MSC in improving cardiac function and structure in a rat model of autoimmune myocarditis.Methods: CEP and CES were prepared through cryopreservation and water-salt extraction processes from placenta and spleen tissues, respectively. CM-MSC was obtained from umbilical mesenchymal stem cells cultured in serum-free medium. All biological agents were standardised for protein content and administered intramuscularly to rats with induced AIM. The rats were divided into six groups, with treatments administered on days 14, 17, 20, 23 and 26 of the experiment. Electrocardiogram (ECG) and echocardiographic studies were performed to assess heart function on day 28.Results: The administration of CEP, CES and CM-MSC significantly improved several echocardiographic parameters. Notably, CM-MSC treatment resulted in the most pronounced effects, including a 6.5 % reduction in the end-diastolic diameter of the left ventricle, a 103.4 % increase in ejection fraction, and a 57.3 % improvement in stroke volume. CEP and CES also improved heart function, but to a lesser extent. These treatments reduced left ventricular dilation, improved myocardial contractility and normalised heart wall thickness, with CM-MSC showing superior cardioprotective effects compared to CEP and CES.Conclusions: The study demonstrates that CEP, CES and CM-MSC have therapeutic potential for improving cardiac function in autoimmune myocarditis. CM-MSC was the most effective in reducing left ventricular dilation and enhancing cardiac output, suggesting its clinical potential for treating autoimmune myocarditis and other cardiovascular diseases.